Flow Cytometry Characterization of Cerebrospinal Fluid Monocytes in Patients With Postoperative Cognitive Dysfunction: A Pilot Study - Berger, Miles; Murdoch, David M; Staats, Janet S; Chan, Cliburn; Thomas, Jake P; Garrigues, Grant E; Browndyke, Jeffrey N; Cooter, Mary; Quinones, Quintin J; Mathew, Joseph P; Weinhold, Kent J (Anesthesia and analgesia, 2019)
Animal models suggest postoperative cognitive dysfunction may be caused by brain monocyte influx. To study this in humans, we developed a flow cytometry panel to profile cerebrospinal fluid (CSF) samples collected before and after major noncardiac surgery in 5 patients ≥60 years of age who developed postoperative cognitive dysfunction and 5 matched controls who did not. We detected 12,654 ± 4895 cells/10 mL of CSF sample (mean ± SD). Patients who developed postoperative cognitive dysfunction showed an increased CSF monocyte/lymphocyte ratio and monocyte chemoattractant protein 1 receptor downregulation on CSF monocytes 24 hours after surgery. These pilot data demonstrate that CSF flow cytometry can be used to study mechanisms of postoperative neurocognitive dysfunction.